2006
DOI: 10.1088/0957-4484/17/23/019
|View full text |Cite
|
Sign up to set email alerts
|

Conducting MWNT/poly(vinyl acetate) composite nanofibres by electrospinning

Abstract: Electrospinning is a relatively simple and versatile method to produce polymer nanofibres and their composites. In this work, functionalized multiwalled carbon nanotubes (f-MWNTs) were used for the fabrication of conducting nanocomposite fibres, in comparison with the composite nanofibres made of unfunctionalized MWNTs (u-MWNTs). Our results showed that the addition of f-MWNTs could improve the dispersion of carbon nanotubes in the polymer solution and therefore result in composite nanofibres with uniform diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 38 publications
2
45
0
1
Order By: Relevance
“…In addition, electrospinning method offers the synthesis polymer/carbon nanotubes (CNTs) nanocomposite fibers without compromising the structural integrity of the individual CNTs [38, 39]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, electrospinning method offers the synthesis polymer/carbon nanotubes (CNTs) nanocomposite fibers without compromising the structural integrity of the individual CNTs [38, 39]. …”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the core component consists almost completely of MWNTs. In the case composites formed by blending MWNTs into a polymer matrix, the MWNTs must form a network structure to conduct current 12,16. We observed that such conductivities become saturated at relatively low MWNT loading.…”
Section: Resultsmentioning
confidence: 81%
“…CNTs, depending on their structural parameters can be conductors or semiconductors 6,17. CNTs obtained from the regular method are usually a blend of conducting and semiconducting materials 19. These parameters change significantly both within a sample and between samples from different batches and labs.…”
Section: Resultsmentioning
confidence: 99%